2018
DOI: 10.3389/fphys.2018.01383
|View full text |Cite
|
Sign up to set email alerts
|

Profibrotic, Electrical, and Calcium-Handling Remodeling of the Atria in Heart Failure Patients With and Without Atrial Fibrillation

Abstract: Atrial fibrillation (AF) and heart failure (HF) are common cardiovascular diseases that often co-exist. Animal models have suggested complex AF-promoting atrial structural, electrical, and Ca2+-handling remodeling in the setting of HF, but data in human samples are scarce, particularly regarding Ca2+-handling remodeling. Here, we evaluated atrial remodeling in patients with severe left ventricular (LV) dysfunction (HFrEF), long-standing persistent (‘chronic’) AF (cAF) or both (HFrEF-cAF), and sinus rhythm cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 67 publications
2
64
2
3
Order By: Relevance
“…We cannot exclude the possibility that PPP1R3A mediates PP1 targeting to proteins other than RyR2 and PLN; however, we believe this is unlikely because PPP1R3A binds to the SR membrane and is therefore not easily accessible to non-SR-bound proteins. 30 Finally, in the present cohort of patients with AF, we did not observe an increase in RyR2 phosphorylation at Ser2808 as reported in some, 8,11,36,46 but not all [47][48][49] previous studies. Differences in type and evolution of the underlying atrial cardiomyopathy may potentially contribute to and explain these inconsistent results.…”
Section: Potential Limitationssupporting
confidence: 72%
“…We cannot exclude the possibility that PPP1R3A mediates PP1 targeting to proteins other than RyR2 and PLN; however, we believe this is unlikely because PPP1R3A binds to the SR membrane and is therefore not easily accessible to non-SR-bound proteins. 30 Finally, in the present cohort of patients with AF, we did not observe an increase in RyR2 phosphorylation at Ser2808 as reported in some, 8,11,36,46 but not all [47][48][49] previous studies. Differences in type and evolution of the underlying atrial cardiomyopathy may potentially contribute to and explain these inconsistent results.…”
Section: Potential Limitationssupporting
confidence: 72%
“…Polyakova et al found increased atrial expression of MMP2, MMP9, and TIMP1, although no differences in TIMP4, in AF patients submitted to a mini-Maze procedure [ 31 ]. Conversely, there were no differences in MMP9 atrial expression in AF patients with heart failure with reduced ejection fraction [ 32 ]. Despite a similar expression of TIMP4 between groups, MMP2/TIMP4 and MMP16/TIMP4 ratios demonstrated a decrease in AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 is the major gap junction channel protein and influences cell's conduction properties, which is related to ischaemic cardioprotection. [23] Since metoprolol regulated Cx43 expression, we further explore whether metoprolol influences intercellular conduction of cardiomyocytes by lucifer yellow dye diffusion assay. As shown in Figure 4c and d, H 2 O 2 treatment led to a slower intercellular conduction, as indicated by the reduced dye diffusion distance.…”
Section: Metoprolol Increases Gap Junction Permeability Through Mir-1mentioning
confidence: 99%